Palestinian Bedouins in Jamil as-Salhut’s Novel al-Mā`iq: A Foucauldian Study of Power Relations - Winaldy Maulidan; Muhammad Khoirul Malik (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2026)
This study examines power relations over the body and mind in Jamīl as-Salḥūt's novel al-Mā`iq, highlighting their importance in understanding mechanisms of discipline and control. It aims to explain how power operates through everyday practices in Palestinian Bedouin society by using Michel Foucault’s theory of power relations. This research employs a descriptive qualitative method with the novel as the primary source of data. The findings show that power in the novel does not operate only through direct authority but also through cultural norms, religious values, political interests, and traditions that regulate both the body and the mind. These forms of power discipline women and men in different ways while encouraging them to internalize social expectations and accepted values. As a result, power becomes part of everyday life, shaping individual behavior, identity, and social relations rather than functioning merely as coercion. This finding supports Foucault’s view that power is embedded in daily social practices and demonstrates how literary texts can reveal the subtle ways in which discipline and normalization operate within a traditional community. This study contributes to Foucauldian literary scholarship by showing how power relations are represented in the cultural setting of a Palestinian Bedouin community, a context that has received limited attention in previous studies. It also highlights the importance of literature as a medium for understanding the relationship between power, culture, and identity in Middle Eastern societies.